2000
DOI: 10.1007/s004670050045
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the ACE gene in Henoch-Schönlein purpura nephritis

Abstract: Individuals with IgA nephropathy (IgAN) who are homozygous for the deletion (D) polymorphism of the gene for angiotensin converting enzyme (ACE) are reported to be at increased risk of progressive renal damage. Since IgAN and Henoch-Schönlein purpura with associated nephritis (HSPN) share a common aetiology, we have investigated this influence in 31 children with HSPN. The distribution of genotypes was as follows: II: 4, ID: 17 and DD: 10 patients. Median length of follow-up was 4.5 years (range 0.5-15.75 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…However, Dudley et al [18] reported no association between disease severity and the ACE DD genotype in children with HSP nephritis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, Dudley et al [18] reported no association between disease severity and the ACE DD genotype in children with HSP nephritis.…”
Section: Discussionmentioning
confidence: 97%
“…The ACE gene deletion polymorphism (DD genotype) is associated with the largest amount of angiotensin converting enzyme and angiotensin II, which has hemodynamic, growth, and prosclerotic effects [7]. The ACE DD genotype has been suggested as an independent cardiovascular risk factor [8,9,10] and also as a predictor of progressive glomerulosclerosis in diabetic nephropathy [11,12,13], IgA nephropathy [14,15,16], and other chronic renal diseases [17,18,19,20,21]. In VUR, contradictory results were reported for the ACE gene polymorphism and reflux nephropathy [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that there is a genetic predisposition to developing HSP and subsequent renal involvement. Multiple factors have been implicated including human leucocyte antigen class II genes, genetic polymorphisms of the renin angiotensin system and cytokines such as IL-1 β [3, 10,28]. HSP is also more common in children with familial Mediterranean fever [26].…”
Section: Aetiologymentioning
confidence: 99%
“…Although some previous studies were unable to confirm any association between ACE I/D gene polymorphism and HSP disease, a study on a Chinese cohort have shown that the frequency of D allele was higher than that of control group. 12,20,21 The ACE I/D SNP was not associated with HSP in our population; however, joint interaction analysis of ACE I/D and CCL2 C-2518T showed a significantly higher frequency of II genotype of ACE I/D in coexistence with TT genotype of CCL2 C-2518T in patients. This joint association shows the possible existence of epistasis between these two genes.…”
Section: Resultsmentioning
confidence: 54%
“…11 Polymorphism of the ACE gene (I/D) and its role in HSP disease has been studied in patients from different populations. 12,13 Considering that HSP disease is a complex disease involving different genetic factors, we planned to evaluate the possible associations of these polymorphisms with the susceptibility to HSP independently and in different joint combinations.…”
mentioning
confidence: 99%